Model of Pontoon by Bamboo Material for Subtituting Land Fill Embankment - Rifqi Brilyant Arief (International Conference on Coastal and Delta Areas, 2015)
This research was intended to find out new way of building foundation which wascompatible to soft soil located around swamp or embankment area. This foundation had to have big bearing capacity, gives small settleent by using bamboo that it was affordable and easy to afford. The foundation had to be visible to work out by the bricklayer and did not need sophisticated technology such as heavy machinery that this could give benefit to low economy community living in the area. This research was specifically to find out proper combination between water and soil where its powerwas mobilized by the foundation, as this has been mobilized by using one of them whether the water (Pontoon Foundation) or the soil itself (Conventional Shallow Foundation). The use of pontoon by far had been limited to raw material (drum). While conventional foundation required, the original soil which would settle significantly because of embankment above it. The method used in the research adopted the use of full-scale testing 1:1 and was done physical test to know the strength with rightcombination to get distribution of bearing capacity between soil and water. This research was located in the soft clay which was still being used as an embankment located in UNISSULA Semarang.